2015
DOI: 10.1038/onc.2015.305
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-specific activatable Myb initiates colon tumorigenesis in mice

Abstract: Transcription factor Myb is overexpressed in most colorectal cancers (CRC). Patients with CRC expressing the highest Myb are more likely to relapse. We previously showed that mono-allelic loss of Myb in an Adenomatous polyposis coli (APC)-driven CRC mouse model (Apc Min/+ ) significantly improves survival. Here we directly investigated the association of Myb with poor prognosis and how Myb co-operates with tumor suppressor genes (TSGs) (Apc) and cell cycle regulator, p27. Here we generated the first intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Myeloblastosis is also required for maintenance of adult stem cells of the colon and brain. In the colon crypts and in colon cancer, it stimulates stem cells required for tissue maintenance and tumor repopulation, respectively . Using a mouse model with inducible tissue specific loss, MYB was also found to be critical for maintenance of neural stem cell progenitors in the adult brain .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloblastosis is also required for maintenance of adult stem cells of the colon and brain. In the colon crypts and in colon cancer, it stimulates stem cells required for tissue maintenance and tumor repopulation, respectively . Using a mouse model with inducible tissue specific loss, MYB was also found to be critical for maintenance of neural stem cell progenitors in the adult brain .…”
Section: Resultsmentioning
confidence: 99%
“…In the colon crypts and in colon cancer, it stimulates stem cells required for tissue maintenance and tumor repopulation, respectively. 111,112 Using a mouse model with inducible tissue specific loss, MYB was also found to be critical for maintenance of neural stem cell progenitors in the adult brain. 113 Interestingly, of MYB's two closely related family members, only MYBL1 expression patterns link it to proliferation of immature neuronal precursor cells.…”
Section: Sox10mentioning
confidence: 99%
“…Actually, among the 7 genes included, several have been reported to be involved in the pathogenesis of colon cancer. Activation of MYB could induce colon tumorigenesis [35], and it was also selected as a target for antineoplastic therapy [36]. MSLN had been accepted to be a candidate biomarker in colon cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although these members share highly conserved DNA-binding domains and binding site specificities, they appear to have different biological roles (62,63). Studies have shown that Myb proteins play important oncogenic roles in a variety of solid tumors (64), including colon tumor (65)(66)(67)(68). MYBL1 is a strong transcriptional activator (69) and is often co-expressed with other members of the myb family (62), but its function is not as well studied as other members.…”
Section: Discussionmentioning
confidence: 99%